The Intermediate State: Revelation 6:9–11 and 20:4–6, 13 in the Light of Daniel 12:2, 13 - Kuryliak, Bohdan; Kuryliak, Ihor (The Biblical Annals, 2025)
In the Book of Revelation, John sees souls under the altar, who then come to life (Rev 6:9–11; 20:4–6, 13). The passages describing the scene are often used as arguments to confirm the existence of a conscious state after death. This article criticises this dualistic interpretation and argues that Dan 12:2, 13 are verses of high importance for the correct interpretation of Rev 6:9–11 and 20:4–6, 13. The article discusses the six parallels between these texts and, based on the Old Testament background, shows that the word ψυχή in Rev 6:9–11 means “blood,” which represents the slain martyrs. The article argues that the teaching on the state of the dead in the Books of Daniel and Revelation is based on a holistic anthropological concept.